The synthetic peptide CIGB-300 modulates CK2-dependent signaling pathways affecting the survival and chemoresistance of non-small cell lung cancer cell lines - Cirigliano, Stéfano Martín (2017)
Background: Lung cancer is the most frequently diagnosed cancer and the leading cause of cancer-related deaths worldwide. Up to 80% of cancer patients are classified as non-small-cell lung cancer (NSCLC) and cisplatin remains as the gold standard chemotherapy treatment, despite its limited efficacy due to both intrinsic and acquired resistance. The CK2 is a Ser/Thr kinase overexpressed in various types of cancer, including lung cancer. CIGB-300 is an antitumor peptide with a novel mechanism of action, since it binds to CK2 substrates thus preventing the enzyme activity. The aim of this work was to analyze the effects of CIGB-300 treatment targeting CK2-dependent signaling pathways in NSCLC cell lines and whether it may help improve current chemotherapy treatment. Methods: The human NSCLC cell lines NCI-H125 and NIH-A549 were used. Tumor spheroids were obtained through the hanging-drop method. A cisplatin resistant A549 cell line was obtained by chronic administration of cisplatin. Cell viability, apoptosis, immunoblotting, immunofluorescence and luciferase reporter assays were used to assess CIGB-300 effects. A luminescent assay was used to monitor proteasome activity. Results: We demonstrated that CIGB-300 induces an anti-proliferative response both in monolayer- and three-dimensional NSCLC models, presenting rapid and complete peptide uptake. This effect was accompanied by the inhibition of the CK2-dependent canonical NF-ΚB pathway, evidenced by reduced RelA/p65 nuclear levels and NF-ΚB protein targets modulation in both lung cancer cell lines, as well as conditionally reduced NF-ΚB transcriptional activity. In addition, NF-ΚB modulation was associated with enhanced proteasome activity, possibly through its α7/C8 subunit. Neither the peptide nor a classical CK2 inhibitor affected cytoplasmic β-CATENIN basal levels. Given that NF-ΚB activation has been linked to cisplatin-induced resistance, we explored whether CIGB-300 could bring additional therapeutic benefits to the standard cisplatin treatment. We established a resistant cell line that showed higher p65 nuclear levels after cisplatin treatment as compared with the parental cell line. Remarkably, the cisplatin-resistant cell line became more sensitive to CIGB-300 treatment. Conclusions: Our data provide new insights into CIGB-300 mechanism of action and suggest clinical potential on current NSCLC therapy.